Tafsir Budaya Asak Budu Ge Saro pada Masyarakat Bangka Belitung dalam Perspektif Pendidikan Anak - Astuti, Sriyati D (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
Asak Budu Ge Saro is a popular proverb of the people of Bangka Belitung. Although in Languange this proverb has positive meaning, but in its use, this proverb is used for other things that give rise to a less positive meaning. Through the analysis of Geertz’s cultural interpretation, this study aims to re discuss this old Bangka Belitung proverb in the Current use of Bangka Belitung Society. This Study will link the proverb asak budu ge saro with children Education. Where in a positive sense, this proverb ia able to be very good advice for children and can be a motivation in early childhood education.